2001
DOI: 10.1029/2000ja000339
|View full text |Cite
|
Sign up to set email alerts
|

The phase structure of very low latitude ULF waves across dawn

Abstract: Abstract. Ultralow frequency (ULF) waves at the geomagnetic equator are studied by using a small magnetometer array and a one-dimensional electromagnetic wave model. Most ULF waves observed at low latitudes have been associated with shear Alfven mode hydromagnetic resonances in the plasmasphere. Near the equator it is difficult to excite these resonances, and the wave activity is attributed to fast mode waves. The phase difference data recorded at longitudinally spaced, equatorial magnetometers shows a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Item 3 above, newly found in this paper, can be rephrased as follows: The H ‐component Pc3 pulsations near the ground magnetic equator have a very small azimuthal wave number ( m ≈ 0.3). The 180° phase shift across 0730 LT (item 4) is very similar to the observational result shown in a case study by Waters et al [2001]; they observed ∼150° phase difference around dawn between POH (Φ = 0.09°, Λ = 229.19°) and YAP (Φ = 1.02°, Λ = 209.42°), which are longitudinally distributed along the dip equator. We have clarified that this sharp phase shift always occurs around 0730 LT slightly off the dip equator (Φ = 3.0–6.2°).…”
Section: Summary and Discussionsupporting
confidence: 84%
“…Item 3 above, newly found in this paper, can be rephrased as follows: The H ‐component Pc3 pulsations near the ground magnetic equator have a very small azimuthal wave number ( m ≈ 0.3). The 180° phase shift across 0730 LT (item 4) is very similar to the observational result shown in a case study by Waters et al [2001]; they observed ∼150° phase difference around dawn between POH (Φ = 0.09°, Λ = 229.19°) and YAP (Φ = 1.02°, Λ = 209.42°), which are longitudinally distributed along the dip equator. We have clarified that this sharp phase shift always occurs around 0730 LT slightly off the dip equator (Φ = 3.0–6.2°).…”
Section: Summary and Discussionsupporting
confidence: 84%
“…9). Waters et al (2001) showed that the vertical propagation effect in the ionosphere, which is controlled by the ionospheric conductivity, and horizontal wave number, can be a cause of the gradual phase shift with longitude of equatorial ULF waves. We suggest two other possibilities.…”
Section: D-to-h Amplitude Ratiomentioning
confidence: 99%
“…At lower latitudes, the fast mode may no longer be evanescent (e.g. Waters et al, 2001) and the full reflection coefficient and mode conversion matrix, including an oblique B 0 , needs to be considered (Sciffer and Waters, 2002).…”
Section: Introductionmentioning
confidence: 99%